Enhancing Student’s Vocabulary by Using Flashcard Media Via Google Classroom During Covid-19 - Sinariati Putri Yani Pasaribu; Riris Debora Hutasoit; Yesi Naomi Sihombing (Universitas Pahlawan Tuanku Tambusai, 2022)
Learning English as a foreign language in Indonesia is not easy, especially for students who came from varies mother tongue. One of the biggest factor in aquiring the language is Vocabulary. This study aims to provide some solutions for Junior High school students to enhance their vocabulary skill to improve their English skill. It was applied a classroom Action Research where the researcher studied the English classroom during learning English Vocabulary in Goodle classroom . The method we have used in this research is descriptive qualitative with data collected through face-to-face observations. It was conducted through 3 cycles and it tested via Google Classroom with junior high school students for 3 CAR cycles. The results showed that flashcards media were very effective in enhancing students' vocabulary